Well child care services in New Zealand : an investigation into the provision and receipt of well child care services in a Hawkes Bay sample : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Nursing at Massey University - Tilah, Morag S W (Massey University, 1998)
Maternal and child care in New Zealand has traditionally been given by a variety of providers from the private and public sector. The reorganisation of the health services has effected all forms of health delivery including maternal and well child care or well child care services. Contracting of services in a competitive environment has been an important feature of the reorganisation process. Ashton (1995) notes that the system of contracting has facilitated the introduction of new approaches to health from new provider groups, which are not necessarily based on primary health care principles. This has led to confusion for providers and consumers alike. In 1996 a new national schedule which described the services recommended for maternal and child care was introduced called WellChild/Tamariki Ora. A questionnaire based on this schedule was administered to a sample of 125 parents of children under five years of age in Hawkes Bay to investigate issues relating to the provision and receipt of well child care services. Descriptive data showed that the major providers of services in the present study were doctors. There were significant differences found in the number of services received across a number of demographic variables such that generally fewer services were received by the less educated, the unemployed, single parent families, and Maori and Pacific Island people. Perceptions about the helpfulness of services received were not related to ratings of the child's health. Parents who received a greater number of Family/Whanau support services rated their children's health more highly. Findings are discussed in relation to the previous literature and recommendations are presented with particular emphasis on the implications for nursing and the role of nurses in providing well child care services.
Keywords: Child health services; Maternal health services; Preventative health services for children; Health promotion; Hawkes Bay, New Zealand